Gender Differences in Cyberbullying Victimization From a Developmental Perspective: An Examination of Risk and Protective Factors. (December 2022) - Lee, Yeungjeom; Harris, Michelle N.; Kim, Jihoon
Although a growing number of studies have examined the underlying mechanisms of cyberbullying victimization, less is known about the gender differences in developmental nature of cyberbullying victimization. This study aims to examine (1) developmental pathways of cyberbullying victimization by gender, and (2) gender differences in the risk and protective factors. Relying on longitudinal data of Korean youth, we found three latent trajectories for girls and four subgroups for boys. In general, results found somewhat different developmental patterns of cyberbullying victimization by gender. Also, results showed both gender similarities and differences in predictors. Peer support was the only consistent factor across boys and girls and there were gendered predictors as well. Implications for practice and suggestions for future research are discussed.